2019
DOI: 10.1111/aogs.13632
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal bromocriptine improves pain, menstrual bleeding and quality of life in women with adenomyosis: A pilot study

Abstract: Introduction Adenomyosis is a benign uterine disease where endometrial glands and stroma are found within the myometrium surrounded by an area of hypertrophic myometrium. Symptomatology includes heavy menstrual bleeding and pelvic pain. The pathogenesis of adenomyosis is not known; however, animal models have shown increased uterine concentration of prolactin as a risk factor. Prolactin acts as a smooth muscle cell mitogen. If prolactin is central to adenomyosis pathogenesis, reducing uterine prolactin could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…108 In humans, higher levels of PRL have been reported in women with than without adenomyosis, 109 and vaginal administration of bromocriptine significantly decreased menstrual bleeding and pain and improved quality of life in women with disease. 110 Mechanisms underlying elevated PRL and PRLR in the pathogenesis of adenomyosis are still unclear. In the normal bovine uterus, endometrial cells are the main source of PRL, whereas in the setting of adenomyosis, it is intensely synthesized by myometrial cells.…”
Section: The Role Of Pituitary Hormonesmentioning
confidence: 99%
“…108 In humans, higher levels of PRL have been reported in women with than without adenomyosis, 109 and vaginal administration of bromocriptine significantly decreased menstrual bleeding and pain and improved quality of life in women with disease. 110 Mechanisms underlying elevated PRL and PRLR in the pathogenesis of adenomyosis are still unclear. In the normal bovine uterus, endometrial cells are the main source of PRL, whereas in the setting of adenomyosis, it is intensely synthesized by myometrial cells.…”
Section: The Role Of Pituitary Hormonesmentioning
confidence: 99%
“…In humans, although vaginal bromocriptine therapy was found to improve adenomyosis symptoms, this study was performed by validated questionnaires without any clinical data. 9 Interestingly, in Yang et al's 10 study, no correlation was found between the PRL levels and uterine volume, but PRL levels declined significantly following ablation therapy in most of the patients. In the present study, no statistically significant difference was found between the percentage of patients with elevated PRL levels with the uterine size ⩽240 cm 3 and >240 cm 3 (p = 0.352).…”
Section: Discussionmentioning
confidence: 90%
“…[6][7][8] In humans, vaginal bromocriptine therapy has been found to reduce menstrual bleeding and pain in adenomyosis. 9 Furthermore, cancer antigen 125 (CA 125) and prolactin (PRL) levels were declined by ultrasound-guided percutaneous microwave ablation therapy in patients with adenomyosis. 10 CA 125 is best known as a marker of ovarian cancer; nevertheless, CA 125 levels were also elevated in adenomyosis, particularly with the enlarged uterine size of >12 gestational weeks or volume beyond 240 cm 3 in a previous study by Sheth and Ray.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of vaginal bromocriptine 46,47 was evaluated in women diagnosed with adenomyosis by either magnetic resonance imaging (MRI) or TVU findings in a single-arm study. 48 Bromocriptine was started at 1.25 mg daily and gradually escalated to a target dose of 5 mg daily. Treatment was continued for 6 months and outcomes evaluated at 3 and 6 months after 5 mg dosing and once more after cessation of bromocriptine for 3 months.…”
Section: Dopamine Agonistsmentioning
confidence: 99%